2005
DOI: 10.1002/marc.200500283
|View full text |Cite
|
Sign up to set email alerts
|

Color Formation and Gelation of Xyloglucan Upon Addition of Iodine Solutions

Abstract: Summary: We developed a novel thermo‐reversible gelation system by mixing xyloglucan with an iodine solution. Xyloglucan dissolves in water to produce a colorless solution. However, the addition of iodine solution induces color and gelation; heating causes the gel to melt and become colorless. According to results from spectroscopic and small‐angle X‐ray scattering experiments, the gelation mechanism was proposed to involve two xyloglucan chains that associate side‐by‐side and incorporate iodine and/or iodide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…The R G,c values for the fresh and aged TSX are about 0.45 ± 0.01 nm (Table 1). These values are comparable to the crosssectional size of TSX as in previous reports and which indicated that TSX exists as a single chain [8,9,27]. The work described here demonstrated that no change occurred in the TSX structure when the sample was aged for a period of up to 24 h. Linear regions also existed in the profile for the mixture containing 0.33% (w/v) EBT (Fig.…”
Section: Saxs Analysessupporting
confidence: 92%
See 1 more Smart Citation
“…The R G,c values for the fresh and aged TSX are about 0.45 ± 0.01 nm (Table 1). These values are comparable to the crosssectional size of TSX as in previous reports and which indicated that TSX exists as a single chain [8,9,27]. The work described here demonstrated that no change occurred in the TSX structure when the sample was aged for a period of up to 24 h. Linear regions also existed in the profile for the mixture containing 0.33% (w/v) EBT (Fig.…”
Section: Saxs Analysessupporting
confidence: 92%
“…In addition, modified TSX has been mixed with other polymers, such as pectin and alginate, for a sustained delivery of drugs by the oral route [5]. Recently, natural TSX was found to form a gel when admixed with some small molecules, such as a sugar, alcohols [6], polyphenol [7], iodine [8], congo red [9] and eriochrome black T (EBT) [10].…”
Section: Introductionmentioning
confidence: 98%
“…Aqueous solutions of tamarind xyloglucan exhibit Newtonian fluidity (Gidley et al 1991), while gel formation can be induced by the addition of alcohols or by partial degalactosylation (reviewed in Yamatoya and Shirakawa 2003;Zhou et al 2006b; see also Nisbet et al 2006;Nishinari et al 2006 for recent references). Xyloglucan also forms complexes with borate (Martin et al 2003), Congo Red dye (Yuguchi et al 2005b), epigallocatechin gallate (Nishinari et al 2006), and I 2 /KI (Yuguchi et al 2005a), which affect rheological properties and gel formation. Indeed, it is the general reaction of xyloglucans with tri-iodide to form a blue-green complex, which caused them to first be described as ''amyloids,'' by analogy with starch (Kooiman 1960).…”
Section: Higher-order Structures and Complexes Of Xyloglucansmentioning
confidence: 98%
“…Recently, natural TSX was reported to be able to form a gel when admixed with small molecular weight compounds, such as sugar, alcohols (Yuguchi et al, 2004), polyphenol (Nitta et al, 2004), iodine (Yuguchi et al, 2005a) and Congo red (Yuguchi et al, 2005b).…”
Section: Introductionmentioning
confidence: 99%